Procyanidin B2: A promising multi-functional food-derived pigment for human diseases. (15th September 2023) - Chen, Junren; Zhong, Kexin; Jing, Yiqi; Liu, Shengmeng; Qin, Siqi; Peng, Fu; Li, Dan; Peng, Cheng
Highlights: Procyanidin B2 (PB2) is a critical natural pigment abundantly available in daily foods. PB2 has various bioactivities, such as anti-oxidation, anti-inflammation, and lipid regulation. PB2 has numerous beneficial potentials on human health, especially metabolic disorders. Abstract: Natural edible pigments play a paramount part in the food industry. Procyanidin B2 (PB2), one of the most representative naturally occurring edible pigments, is usually isolated from the seeds, fruits, and leaves of lots of common plants, such as grapes, Hawthorn, black soybean, as well as blueberry, and functions as a food additive in daily life. Notably, PB2 has numerous bioactivities and possesses the potential to treat/prevent a wide range of human diseases, such as diabetes mellitus, diabetic complications, atherosclerosis, and non-alcoholic fatty liver disease, and the underlying mechanisms were partially elucidated, including mediating signaling pathways like NF-κB, MAPK, PI3K/Akt, apoptotic axis, and Nrf-2/HO-1. This paper presents a review of the natural sources, bioactivities, and the therapeutic/preventive potential of PB2 and the possible mechanisms, with the aim of promoting the development of PB2 as a functional food and providing references for its clinical application in the treatment of diseases.